Durabilidade de polietileno em vinhaça quente e fresca em usina de açúcar e álcool - Buaszczyk, Gianna (2013)
Geomembranes are polymeric sheets widely used in vinasse ponds to prevent contamination of soil. Long-term durability is expected, since failure can result in environmental impact. Smooth black commercial geomembranes and injected molded plaques manufactured using different polyethylene resins were exposed to hot and fresh vinasse at an ethanol plant. Mechanical, thermal and structural changes were evaluated along 245 days of exposure to the effluent. Results showed that geomembranes are in the first step of degradation process, when it is observed depletion of antioxidants with no modification of mechanical properties. First stage of service life in hot and fresh vinasse was estimated in 4,3 years for the geomembrane 1 mm thick and 5 years for geomembrane of 2 mm. For the injected molded plaques, service life was estimated in 4,4 up to 6 years for the resins compounded with 2,5% of carbon black. The longer durability was observed for the bimodal metallocene/octene-1 comonomer from Dow Solution polymerization process. Incipient degradation was observed after 153 days, which occurred preferentially in the lower molecular weight by branching. The proposed methodology, based on injected molded plaques and their exposure in the field conditions, was validated to assess the stage of antioxidants depletion of service life of different polyethylene resins.